Towards recombinantly produced milk proteins: Physicochemical and emulsifying properties of engineered whey protein beta-lactoglobulin variants. (January 2021) - Keppler, Julia K.; Heyse, Anja; Scheidler, Eva; Uttinger, Maximilian J.; Fitzner, Laura; Jandt, Uwe; Heyn, Timon R.; Lautenbach, Vanessa; Loch, Joanna I.; Lohr, Jonas; Kieserling, Helena; Günther, Gabriele; et al.
Graphical abstract: Image 1 Highlights: Two recombinant beta-lactoglobulin (BLG) B variants were produced in E. coli . Production/isolation resulted in native BLG without post-translational modifications. Properties of recombinant variants were compared to commercial BLG B and BLG AB. Minor differences in solubility and interface adsorption behavior were evident. Genetically engineered and natural BLGs show similar emulsifying properties.